Indication Géographique De L’huile De Palme De “Man’’ (District Des Montagnes-Côte d’Ivoire) : Une Analyse Comparative Des Propriétés PhysicoChimiques Et Profils En Acides Gras De Quelques Huiles De Palme Rouge Artisanales Ivoiriennes - Kouakou, N’Goran David Vincent; Kouassi, Kouakou Amos; Angbo-Kouakou, Cho Euphrasie Monique; Ahongo, Diane Yéléhi; Jean, Pohé; Adima, Amissa Augustin (European Scientific Journal, ESJ, 2017)
Artisanal crude palm oil (ACPO) of “Man’’ (District des Montagnes, Ivory Coast) enjoys a national and international reputation for quality among consumers. In order to record this local product as a geographical indication product, a study aimed to compare the physicochemical parameters and fatty acid profiles of some ACPO samples from the “Dura” variety collected in the districts of Lagunes, Sassandra-Marahoué, Bas-Sassandra and Montagnes, was conducted. It shows that the samples collected in the District des Montagnes have a low density (0.949±0.018 g/ml), a high iodine value (63.9±0.5 g of iodine/100 g of fat) and a low peroxide value (1.2±0.2 meqO 2 / kg of fat), a slightly high pH (3.1±0.3) than those in other districts. Furthermore, these samples exhibit the lowest levels of saturated fatty acid (34.8%). The principal component analysis performed on all parameters studied, shows that the samples are of ACPO from "Man" have a more uniform profile, a symbol of a common ancestral know-how and that its deserves a Geographical Indication